Foundations of Respiratory Medicine (Springer International Publishing, 2018)
This book is a comprehensive resource to approach the diagnosis and treatment of respiratory conditions. It bridges the gap between the required core knowledge and the emerging areas where new investigative techniques and treatments are already impacting on everyday clinical practice. Common conditions such as lung cancer, asthma, COPD, respiratory infection, and thromboembolic disease are dealt with in detail as well as more specialist areas such as interstitial lung disease, pulmonary hypertension, sleep and ventilatory failure. The authors are all practising specialists in their subject areas and discuss underlying physiological mechanisms, clinical approaches, evidence-based guidelines, and areas of uncertainty for each topic. The chapters are well illustrated by high quality multimodality imaging and show examples of both classic and unusual conditions with descriptive legends. The format is ideal for post-graduate and doctors who are completing their training in respiratory medicine.